2011
DOI: 10.1001/archinternmed.2011.561
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Quality of Life With Supervised Exercise Training in Subjects With Type 2 Diabetes Mellitus

Abstract: lower for the intervention than for the control group. Although this difference was not statistically significant, it corresponds with an estimated 0.4 life-years gained. From the British Doctors study 1 it is possible to estimate that an intervention that yielded an increased cessation rate at the 12-month follow-up of 30% (39% vs 9%) in smokers with the age distribution represented in this study would be expected to yield approximately 0.8 lifeyears. 9 The Table also shows lower hazard ratios for many specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…The main analyses on the primary and secondary endpoints, i.e. changes in hemoglobin (Hb) A 1c and other modifiable cardiovascular risk factors, physical fitness, and quality of life, have been reported elsewhere [19,22,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…The main analyses on the primary and secondary endpoints, i.e. changes in hemoglobin (Hb) A 1c and other modifiable cardiovascular risk factors, physical fitness, and quality of life, have been reported elsewhere [19,22,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes included improvements in other modifiable CVD risk factors, change in the number and/or dosage of glucose-, lipid-, and BP-lowering drugs, UK Prospective Diabetes Study (UKPDS) global CHD 10-year risk scores, health-related quality-of-life, and the relationship between changes in physical fitness and modifiable CVD risk factors. Results of this trial have been reported elsewhere (8,9), except those concerning the relation of physical fitness with modifiable CVD risk factors.…”
Section: Methodsmentioning
confidence: 95%
“…In addition, physical and mental health–related quality-of-life improved significantly with supervised exercise, but not with counseling alone (9). The incremental health benefits of supervised exercise beyond those of counseling alone were associated with a higher volume of PA, both total and unsupervised, and more marked improvements in physical fitness (8).…”
mentioning
confidence: 99%
“…Overall, 1,261 articles were retrieved from electronic databases and manual searches, 161 articles were included based on review of the title, 33 based on review of the abstract, and 20 [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] based on review of the full text article (ESM Fig. 1).…”
Section: Description Of Studiesmentioning
confidence: 99%